ALTERNATIVE METHODS OF TEACHING PHYSICS - Bañas, Norade A. (International Journal of Psychosocial Rehabilitation, 2020)
that students learn better makes the effort of meeting the challenges worthwhile. To meet this, the study “Alternative Methods of Teaching Physics” may contribute. The study is modeled by incorporated indigenous folk motifs into modern forms. The researcher identified folk games that can demonstrate physics principles and designed class instructions in teaching physics using folk games, power point presentation, and lecture with board work. The purpose was to determine and compare the performance of physics students.All participants were given opportunities to experiential learning. However, males tended to be underrepresented. Subjects were in their typical age in college, many were “above average”. Performance levels improvedamong different groups.All had comparable performance but significantly improved only in groups between “below” and “above” average.Three instructional methods stand out. It has shown to be effective in raising attainment and contributes to increased student motivation because instructional approaches used has maximized student learning. Pedagogy for physics learning could be more effective and inclusive when physics is taught and learned in contexts in which students can make links between their existing knowledge, experiences and when students are engaged in thinking physics during the learning tasks.If a follow-up study will be pursued, it might make links more evident.